α-sober spaces via the orthogonal closure operator - Sousa, Lurdes (2015)
Each ordinal alpha equipped with the upper topology is a T0-space. It is well known that for alpha=2 the reflective hull of alpha in Top0 is the subcategory of sober spaces. Here, we define alpha-sober space for every ordinal alpha in such a way that the reflective hull of alpha in Top0 is the subcategory of alpha-sober spaces. Moreover, we obtain an order-preserving bijective correspondence between a proper class of ordinals and the corresponding (epi)reflective hulls. Our main tool is the concept of orthogonal closure operator, introduced by the authour in a previous paper.